Kegiatan Majelis Ta’lim Di Masjid Al Manaar Jorong Gatah Magek Kecamatan Tilatang Kamang - Sulfan, Sebastian; Fauzan, Fauzan; Charles, Charles; Hayati, Hayati (ANTHOR: Education and Learning Journal, 2023)
A mosque is a place of worship for Muslims. Worship activities here have a broad meaning, notonly for praying and reciting but for all activities that can bring benefit to the world and the hereafter. Mosques can also be used as a means of informal education for people who cannotattend formal education, and are not bound by age, whether old or young, therefore it is necessary to hold a ta'lim assembly. The ta'lim assembly is an informal Islamic educational institution that has its curriculum, organized on a scale and regularly followed by a relatively large congregation, aiming to foster and develop as well as enlightenment about life. With the majlis ta'lim activities in the mosque, the congregation or the community can take part in activities to improve the quality of knowledge and worship activities that can be carried out more optimally. The research that the author does is field research (field research). The approach used to conduct research is a qualitative approach. And the key informants in this research are mosque administrators, and supporting informants are the congregation or members of the ta'lim assembly. The techniques used to collect data are observation and interviews, after the data is collected it is processed using qualitative descriptive techniques. Based on the results of the research that has been carried out, it is known that the implementation of the ta'lim assembly activities has gone well and smoothly, it can be seen from the enthusiasm and desire of the congregation in participating in the ta'lim assembly activities, it can be seen from the presence of the congregation in participating in the activities. ta'lim assembly. However, there are still some shortcomings in the management of itsactivities where the congregation is less solemn in carrying out every activity carried out, it can beseen from the congregation there are still chatting when listening to the chanting of the holy versesof the Koran and not focusing when participating in lecture activities because they feel the contentof the lecture is not good or the teacher's language is not understood.